Recent Advances in Nutrition for Disease Prevention and Sports Performance Enhancement - Valenzuela, Pedro L. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Growing evidence supports the important role of nutrition in health and performance. Nutritional interventions, alone or in combination with physical exercise, have proven effective for reducing the incidence of different chronic diseases and their associated risk factors (e.g., obesity, diabetes, hypertension, hypercholesterolemia). A healthy diet also seems to prevent many of the detrimental consequences of aging, notably sarcopenia and frailty. On the other hand, diet has been reported to influence physical performance, with nutrition, including nutritional supplements, being a cornerstone in the armamentarium of athletes. The role of nutrition seems, therefore, wide; however, although research is rapidly growing, controversy and debate still exists as to the optimal nutritional strategies for disease prevention and sports performance enhancement. The present Special Issue aimed to report recent findings on the role of nutrition in disease prevention and sports performance enhancement, as well as to summarize current evidence on these topics.